Review of Cooling and Lubrication Technology of High-speed Motorized Spindle - DAI Ye; ZHANG Chao yu; PAN Gao feng; DENG Hao; CHEN Xin da (Journal of Harbin University of Science and Technology, 2023)
The temperature rise of high-speed motorized spindle due to heat dissipation efficiency is an important factor leading to the problem of thermal deformation, which is one of the main factors affecting the machining accuracy, so it is crucial to study its cooling and lubrication system. In order to discuss the research progress of the cooling and lubrication technology of high-speed motorized spindles in recent years, a thermal characterization was carried out around the internal heat generation and heat transfer mechanism of high-speed motorized spindles as an object. Combined with the research of domestic and foreign scholars on the cooling and lubrication technology of motorized spindle, the methods, principles, advantages and disadvantages, and applications of different cooling methods in the cooling and lubrication technology of high-speed motorized spindle are elaborated respectively from the aspects of motor and bearing. At the same time, the main problems existing in the research are analyzed, and the outlook for future research is made.